The theory of everything else: a voyage into the world of the weird - Schreiber, Dan (Mudlark, 2022)
"A collection of the world's most mind-boggling, thought-provoking and downright hilarious theories - by the co-host of the UK's most downloaded podcast No Such Thing As A Fish, Dan Schreiber. Why are we here? Do ghosts exist? Will we ever travel back in time? Are we being visited by extraterrestrials? Will we ever talk to animals? Are we being told the truth? Are mysterious creatures roaming the Earth? And why, when you're in the shower, does the shower-curtain always billow in towards you? We don't know the answers to any of these questions (that includes the shower-curtain one, which is a mystery that has eluded scientists for decades, and which they are still trying to solve). But don't worry, no matter what questions you have, you can bet on the fact that there is someone (or something) out there, investigating it on your behalf - and this book collects their latest findings. From the Silicon Valley tech billionaires currently trying to work out whether or not the universe is one giant video game simulation; to the self-proclaimed community of Italian time-travellers who are trying to save the world from destruction; The Theory of Everything Else will act as a handbook for those who want to think differently"--Publisher's description